Building community together: A study of inter-neighborhood collaboration and development in Cincinnati, Ohio. Issue 2 (15th March 2018) - Olberding, Julie Cencula; McIntyre Miller, Whitney
Abstract: This study focuses on the joint development efforts of two neighborhoods in Cincinnati, Ohio, US. Focusing on the initial stages of the joint development process, this article analyzes the first three collaborative meetings linking the two communities together. This study demonstrates short-term outcomes from each meeting, as well as longer term data – both quantitative and qualitative – from a survey of nearly 60 participants. Findings demonstrate that the meetings resulted in the identification of assets and challenges in both neighborhoods, as well as strategies and ideas for improving them. In addition, the survey found that the inter-neighborhood meetings enhanced not only participants' interest in community engagement, but also their actual behavior in terms of attending community events, shopping local, and informing friends and neighbors about the community. Further, many survey respondents observed improvements in the overall relationship between the two neighborhoods.